REVITALIZING ACADEMIA: UNPACKING THE NATIONAL EDUCATION POLICY 2020 - Harshith Divakar, (EPRA International Journal of Research and Development (IJRD), 2024)
Purpose: This study aims to delve into the intricate connections between India's National Education Policy 2020 (NEP) and the future of learning, offering a comprehensive analysis of the policy's objectives, challenges, and transformative potential in reshaping higher education institutions. By exploring the academic nuances influenced by the NEP, the research seeks to contribute valuable insights into the evolving educational landscape. Through a multidimensional approach encompassing literature review, policy analysis, and stakeholder interviews, the study endeavors to provide a nuanced understanding of how the NEP is poised to redefine educational paradigms, fostering innovation, inclusivity, and global competitiveness. Ultimately, the purpose is to shed light on the broader implications of the NEP, offering a foundation for informed discourse and strategic decision-making in the realm of Indian higher education. Design/Methodology/Approach: Employing a comprehensive review of literature, policy analysis, and stakeholder interviews, the study synthesizes diverse perspectives to construct a holistic understanding of the NEP's influence. Findings/Result: The NEP acts as a transformative force, catalyzing an educational metamorphosis marked by heightened innovation, enhanced inclusivity, and bolstered global competitiveness. This study, drawing from extensive research, underscores the policy's pivotal role in reshaping higher education institutions. The NEP's influence is discerned through its capacity to instigate positive changes that align with the evolving needs of a dynamic academic landscape, positioning India on a trajectory of educational excellence and global relevance. Originality/Value: This research uniquely explores NEP's impact on Indian higher education, offering valuable insights for informed decision-making.